Pengembangan Media Komik Digital Interaktif: “Daerahku dan Kekayaan Alamnya” dengan Pendekatan Berdiferensiasi - Lintang Kirana Leokiss Wijaya; Barokah Isdaryanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the scarcity of technology-based learning media for natural and social sciences learning tailored to the diverse learning needs of fourth-grade students in Semarang, particularly in regards to regional natural resource potential. The primary objective is to design, evaluate the feasibility, and assess the effectiveness of Interactive Digital Comic media with a differentiated approach. This development research uses the Research and Development (R&D) method with the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation phases. The feasibility assessment by material experts and media experts yielded a percentage of 92.85% and 87.50%, respectively, rating the media as "Very Feasible" based on criteria such as content accuracy, instructional design, and multimedia integration. The effectiveness of the media was evaluated using a quasi-experimental design with a paired sample t-test and N-Gain test. The results showed a significant difference in average student learning outcomes (sig. (2-tailed) = 0.000 < 0.005) and an N-Gain value of 0.82, indicating a significant average increase and high criteria. This study demonstrates the potential of Interactive Digital Comic media to enhance student learning outcomes and engagement in natural and social sciences learning, providing an engaging and interactive learning experience and catering to diverse learning needs.